2012
DOI: 10.26719/2012.18.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and beliefs towards HIV/AIDS among students of health institutes in Sana’a city

Abstract: Students of health-related subjects have an important role in national strategies on HIV/AIDS prevention. This study assessed the knowledge, attitudes and beliefs towards HIV/AIDS among students at health institutes in Sana'a city, Yemen. A descriptive cross-sectional questionnaire survey was conducted on 600 students selected by cluster sampling. Students had a moderate level of HIV/AIDS knowledge (an average of 67.6% were correct on all items). Nevertheless, 82.3% knew that HIV could be transmitted by sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
36
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 11 publications
11
36
3
Order By: Relevance
“…Overall the HIV/AIDS knowledge of the respondents in this study was moderate. The finding of moderate level of HIV/AIDS knowledge in this study is in line with studies performed elsewhere [18] [19]. The level of HIV/ AIDS knowledge in this study is however lower compared to that of nursing students in Japan [20] and India [21] in which HIV/AIDS knowledge was observed to be very high.…”
Section: Discussionsupporting
confidence: 89%
“…Overall the HIV/AIDS knowledge of the respondents in this study was moderate. The finding of moderate level of HIV/AIDS knowledge in this study is in line with studies performed elsewhere [18] [19]. The level of HIV/ AIDS knowledge in this study is however lower compared to that of nursing students in Japan [20] and India [21] in which HIV/AIDS knowledge was observed to be very high.…”
Section: Discussionsupporting
confidence: 89%
“…The literature review of nursing students' level of knowledge of HIV in different countries yields varying results. Whereas some studies reported large knowledge gaps, 8,9,14 others reported a moderate level of knowledge 5,6 or even a good level of knowledge. 7,10 In the present study, while students' overall knowledge level was moderate, a weak area was knowledge of safe practices for health care providers caring for HIV-infected patients.…”
Section: Discussionmentioning
confidence: 90%
“…[5][6][7][8][11][12][13]20 Students in our study were found to express low willingness to take part in surgical nursing procedures involving contact with bodily fluids of HIV-infected patients. Durkin 21 also noted variations in American nursing students' comfort level when providing care to these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the contrary, other studies conducted among students showed poor knowledge, favorable attitude and poor practices towards HIV/AIDS and the study highlighted misconceptions about preventive methods of HIV transmission and risky sexual practices which need to be addressed [23,24].…”
Section: Introductionmentioning
confidence: 97%